Correlation between Self-Talk and Emotional Regulation Among Student Volleyball Athletes - Musyarofah, Amelia; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aims to determine the relationship between self-talk and emotion regulation in volleyball student athletes. Materials and methods. This study uses quantitative descriptive research methods and designs. The instrument used was a questionnaire to measure self-talk using a self-talk scale (STS) of 9 items and a scale of emotion regulation and self-talk of 6 items for each participant, with a score for each item using 5 points. The frequency scale (1 = strongly disagree, 5 = strongly disagree, 5 = strongly disagree, maximum 1 = strongly agree) was administered to the sample once. We performed data processing and analysis in the form of statistical description, normality test using Shapiro-Wilk Test, and correlation test using Spearman-Rank Test. Results. The results showed that there was a significant relationship between self talk and emotion regulation in volleyball student athletes. The relationship between the two variables has a very strong correlation level. Student volleyball athletes have a percentage of emotion regulation ability of 73.3% and self talk of 70.8%. Conclusion. This study concludes that self-talk has an important role in regulating the emotions of student athletes to achieve the goals they want to achieve, namely sports achievement. Efforts to achieve the best performance in match practice, self-talk and emotion regulation are two main aspects that need to be considered.